Optimization of the number of call center operators - Pistunov, Igor (My University, 2021)
Abstract. The intensity of receiving orders from customers was determined by statistical research. The intensity of orders by month is described by a nonlinear transcendental model. Queue theory allowed us to formulate the problem of finding the optimal number of operators serving customers in the call center for a confidence level of 0.95. The economic effect is calculated.
Keywords: queuing theory; order statistics.; optimization of the number of operators.